2016
DOI: 10.5863/1551-6776-21.5.419
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Tolerability of Intermittent Intravenous Sildenafil in Pediatric Patients With Pulmonary Hypertension

Abstract: The primary purpose of this study was to determine the tolerability of intermittent intravenous (IV) sildenafil for the treatment of pulmonary hypertension in pediatric patients. Secondary objectives were to evaluate parameters related to efficacy. METHODS: This was a retrospective chart review from January 2013 to August 2014 of pediatric patients under age 18 years treated with intermittent doses of IV sildenafil for pulmonary hypertension. Patients were excluded if they were over age 18 years or received si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…[ 28 ] And PHT is defined by an imbalance with an increase in pulmonary vascular resistance and pulmonary artery pressures. [ 29 ] This study explored the effect of miR-130a in OSAHS-associated PHT by targeting the GAX gene, our findings validate that miR-130a might limited the expression of GAX and induced OSAHS-associated PHT. A previous study has identified that many different pathogeneses, including hepatocellular carcinoma, cervical cancer, and ovarian cancer, were caused by miR-130a, and many genes which have a strong relationship with different cancer pathways have been identified and validated as targeted genes of miR-130a, such as the GAX gene.…”
Section: Discussionmentioning
confidence: 53%
“…[ 28 ] And PHT is defined by an imbalance with an increase in pulmonary vascular resistance and pulmonary artery pressures. [ 29 ] This study explored the effect of miR-130a in OSAHS-associated PHT by targeting the GAX gene, our findings validate that miR-130a might limited the expression of GAX and induced OSAHS-associated PHT. A previous study has identified that many different pathogeneses, including hepatocellular carcinoma, cervical cancer, and ovarian cancer, were caused by miR-130a, and many genes which have a strong relationship with different cancer pathways have been identified and validated as targeted genes of miR-130a, such as the GAX gene.…”
Section: Discussionmentioning
confidence: 53%
“…5 Intermittent IV sildenafil has demonstrated efficacy in various studies, 6 however hypotension is a reported adverse effect. 7 Studies investigating IV versus oral delivery have not demonstrated significant differences in safety outcomes. 8 Slower administration of IV sildenafil over longer infusion periods has been suggested as a way of avoiding the acute systemic vasodilatory effects of more rapid bolus dosing.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, however, the FDA clarified this warning, stating that there may be situations in which the risk‐benefit profile may be acceptable in individual children, although it is still not recommended (https://www.fda.gov/drugs/drugsafety/ucm390876.htm). Additional pediatric trials of sildenafil in PAH have been performed but are not discussed here because of low patient numbers and/or lack of placebo control …”
Section: Current Management Of Pediatric Pahmentioning
confidence: 99%